Fundamental factors that motivate engineering bachelors to become professors in Brazil (Research, Society and Development, 2022)
In the current scenario, it is clear that a considerable portion of Bachelors in Engineering choose to follow the path of teaching. In this context, the present work aims to discuss the main factors that motivate Bachelors in Engineering to be interested in following the path of teaching in Brazil. Even some professionals who already have a consolidated career in the field of Engineering, at some point start to exercise the teaching activity in parallel with their first area of ​​expertise. Some recent graduates also seek to tread the paths of teaching, even without having entered the job market as engineers, both because of the difficulty of getting an opportunity to establish themselves in the field, and because they identify more with the educational segment. Another fundamental factor, in this context, is the growing implementation of technical, technologist and undergraduate courses in Brazil, which increasingly demand professionals trained in Engineering to teach most of the technical subjects that make up the curriculum of these courses.